Penyelesaian Sengketa pada Suku Osing - Al Arif F, M. Noor Fajar; Hamidi, Jazim; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
This study aims to describe the legal phenomena and ways of resolving disputes in the Osing Tribe. The Osing tribe is a tribe that has adapted to technology and modern life. This research is included in the type of qualitative research that is descriptive in nature. The type of research description used is the survey method. In collecting data, a dialogic interview method is used. Interviews were conducted informally on 3 (three) people who were considered to be aware of the latest problems and the Osing Tribe consensus to be studied. The results of this study show that the osing tribe lives in harmony, side by side and still maintains its customary law. The Osing tribe even though it has interacted with technology and the modern world but in resolving disputes / disputes prioritizes customary law compared to state law. The dispute resolution in the Osing Tribe seems not well organized in terms of institutions. Therefore the Osing Tribe should restore the function of the Kemiren Osing Community Institution (LAMUK) not only as a consultation institution to carry out rituals but also as a dispute settlement institution because the functioning of LAMUK will be one of the characteristics of the Osing Tribe in the legal sphere.